An experimental and theoretical study toward the synthesis, structure and thermal decomposition of some phenyl tetrazoles - Atakol, Arda; Svoboda, Ingrid; Akay, Mehmet Abdulkadi̇r; Atakol, Orhan; Aydiner, Burcu; Öz, Sevi̇; Yilmaz, Nurdane (Springer Science and Business Media LLC, 2014)
1-phenyl-1H-tetrazole (I), 1(2-chlorophenyl)-1H-tetrazole (II), 1(4-chlorophenyl)-1H-tetrazole (III), 1(4-hydroxyphenyl)-1H-tetrazole (IV), 1(4-methoxyphenyl)-1H-tetrazole (V), 1(4-nitrophenyl)-1H-tetrazole (VI), 1(2-pyridyl)-1H-tetrazole (VII), and bis-1,4-tetrazol-1-yl benzene (VIII) were prepared from aniline, 2-chloro aniline, 4-chloro aniline, 4-hydroxy aniline, 4-methoxy aniline, 4-nitro aniline, 2-aminopyridine, and 1,4-phenylendiamine and characterized by Infrared spectroscopy, elemental analysis, mass spectrometry, 1H Nuclear Magnetic Resonance, and 13C Nuclear Magnetic Resonance spectroscopy. Suitable crystals of compounds I, II, IV, V, and VI were obtained and their molecular structures were determined using single crystal X-ray Diffraction. All tetrazole compounds were also investigated using Thermogravimetry–Differential Thermal Analysis. At temperatures between 190–240 °C, the tetrazole ring decomposed exothermically. The decomposition products were estimated by relating the mass loss data and IR spectroscopy results of the residue with N2 release and isonitrile formation as outcome of thermal decomposition. The heat of the exothermic decomposition was measured by Differential Scanning Calorimetry. Optimizations and frequency analyses of all tetrazole compounds were performed at the B3LYP/cc-pVDZ level of theory which are DFT-based structures. The optimum geometries of tetrazole compounds were enlightened with the help of Gaussian 09 pocket program. The enthalpies of formation for solid state were calculated theoretically by CBS-4 M algorithm. The calculated results were compared with the experimental data obtained from DSC study. It was seen that the enthalpies of decomposition of compounds II, III, IV, and V were in good agreement with the theoretical values. However, decomposition of compounds I, VI, VII, and VIII showed significant variation from the theoretical calculations.
Keywords: 3. Good health